2010
DOI: 10.1088/0960-1317/20/8/085022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of epitaxial Pb(Zr,Ti)O3thin films deposited by pulsed laser deposition on silicon cantilevers

Abstract: This paper reports on the piezoelectric-microelectromechanical system micro-fabrication process and the behavior of piezoelectric stacks actuated silicon cantilevers. All oxide layers in the piezoelectric stacks, such as buffer-layer/bottom-electrode/film/top-electrode: YSZ/SrRuO 3 /Pb(Zr,Ti) 3 /SrRuO 3 , were grown epitaxially on the Si template of silicon-on-insulator substrates by pulsed laser deposition. By using an analytical model and finite element simulation, the initial bending of the cantilevers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…Figure 7 shows the measured current (blue curve). By integrating the current the polarization hysteresis loop can be calculated [6] which is also shown in the figure (red curve). It can be concluded that the coercive field Ec is around 21kV/cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the measured current (blue curve). By integrating the current the polarization hysteresis loop can be calculated [6] which is also shown in the figure (red curve). It can be concluded that the coercive field Ec is around 21kV/cm.…”
Section: Resultsmentioning
confidence: 99%
“…The PLD deposition process has been described in [6]. After deposition of these layers we have the cross section shown in Figure 5(d).…”
Section: Fabricationmentioning
confidence: 99%
“…The integration of these epitaxial functional oxides with silicon substrates offers significant opportunities for applications. [1][2][3][4][5][6][7][8] Among them are micro-electromechanical systems (MEMS) based on epitaxial piezoelectric layers [9][10][11][12][13] and suspended bolometers based on epitaxial La 0.7 Sr 0.3 MnO 3 thin films. 14 The use of silicon substrates greatly facilitates the fabrication of MEMS and suspended bolometers, where three-dimensional structures can be efficiently realized by volume silicon micromachining using conventional techniques such as isotropic etching in alkaline solutions (KOH, TMAH, etc.)…”
mentioning
confidence: 99%
“…Conventional epitaxial piezo-MEMS devices fabricated using silicon on insulator (SOI) as substrate material contains relatively thicker (typically 3-50 μm) top Si layer from the substrate on the bottom side of the device [59]. This residual Si layer makes the MEMS devices heavier, often reducing their functional performances, for example the limit of detection (LOD) when used as mass sensors [60].…”
Section: Free-standing Epitaxial Memsmentioning
confidence: 99%
“…These substrates are comprised of two Si crystal (with varying thickness, often the thicker one at bottom) sandwiching an intermediate SiO 2 layer, termed as buried oxide layer (BOX). Figure 5.1 shows a typical fabrication scheme for fabrication of epitaxial PZT MEMS devices on SOI substrates [59]. The fabrication strategy requires back-side etching of the bottom Si layer prior to high temperature deposition of the oxide stack, mostly utilizing dry reactive ion etching.…”
Section: Lift-off Fabrication Of Free-standing Epitaxial Pzt Mems Devmentioning
confidence: 99%